The Effectiveness Of Stem Problem-based Learning Module On Self-efficacy, Interest And Achievement In Biology Among Senior Secondary School Students In Nigeria - Tudu, Usman Gado Birnin (2023)
This study involves two phases, namely, (i) developing a STEM problem-based learning module (STEM-PBLM) using the ADDIE and 3C3R models for Form 4 secondary school students learning diffusion and osmosis concepts. The second phase (ii) tests the effectiveness and suitability of the module (STEM-PBLM) in increasing the self-efficacy, interest, and achievement of students. The study used a quasi-experimental, non-equivalent control group design. The sample of the study consisted of 80 students (48 boys and 32 girls) from two public schools in Kebbi, Nigeria. Both the experimental and control groups were composed of 40 students. The research data consists of a combination of quantitative and qualitative data. Six instruments were used in data collection: (i) the Self-efficacy in Learning Biology Questionnaire (SLBQ); (ii) the Interest in Learning Biology Questionnaire (ILBQ); (iii) the Diffusion and Osmosis Achievement Test (DOAT); (iv) the Teacher Survey Questionnaire (TSQ); (v) the Student Interview Protocol (SIP); and (vi) the Teacher Interview Protocol (TIP). Quantitative data was obtained from the pre-test, post-test, and delayed post-test. On the other hand, qualitative data was obtained from document analysis of teachers' schemes of work and lesson plans, analysis of biology textbooks, and interviews with students and teachers.